The Impact of the Mediatization of Nahdlatul Ulama’s Controversial Issues on the Transformation of Islamic Education in Indonesia - Saputri, Alfiyan; Nugroho , Adi (Al Ulya: Jurnal Pendidikan Islam, 2026)
The mediatization of controversial issues involving major religious organizations in Indonesia increasingly shapes how the public perceives these organizations' roles, authority, and institutional legitimacy, including in the realm of Islamic education within the digital public sphere. News coverage of Nahdlatul Ulama (NU) not only reflects the organization’s dynamics but also has the potential to influence public perception of its contribution to the transformation of Islamic education. This study aims to analyze how online media coverage of controversial issues involving Nahdlatul Ulama (NU) shapes public perceptions of the organization and its impact on the transformation of Islamic education in Indonesia. The study employs a constructivist approach using qualitative content analysis of 30 articles selected from 300 online media articles published between May and December 2025, chosen based on relevance criteria. Data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions, supported by Discourse Network Analysis (DNA) to map discourse relations and media framing patterns. The results of the study reveal a polarization of discourse between mainstream media—which tends to produce problematic and critical frames of NU—and NU-affiliated media, which emphasizes affirmative and legitimizing narratives. The findings also reveal that NU education's role as an agent of social and educational transformation is often marginalized. This situation has the potential to influence shifts in public perception regarding the symbolic legitimacy of NU education in the digital public sphere. This study contributes to the study of the mediatization of religion by focusing on media discourse analysis.